SUSTAINABILITY IN RETAIL STORE: ANALYSIS OF DETERMINING FACTORS OF GREEN PURCHASE DECISION ON IKEA’S CONSUMERS - Cynthia Anna Wijayanti; Erik Osmond (Journal of Global Business and Management Review, 2026)
Public concern about environmental sustainability has increasingly shaped consumer behavior, especially as buyers evaluate products based on their ecological consequences. This study examines the factors that determine Green Purchase Decision among IKEA consumers in the Jabodetabek area. The predictors analysed are Environmental Concern, Green Perceived Benefit, Green Perceived Quality, Green Price Awareness, Green Purchase Willingness, and Future Green Estimation. A quantitative survey was conducted with 273 IKEA customers selected through purposive sampling, and the data were analysed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that Environmental Concern, Green Perceived Quality, Green Purchase Willingness, and Future Green Estimation have positive and significant effects on Green Purchase Decision. Conversely, Green Perceived Benefit and Green Price Awareness do not significantly affect Green Purchase Decision. These findings suggest that sustainability communication, environmental education, and consumer engagement should be strengthened to increase environmental concern and willingness to purchase green products.